Rasionalitas Penggunaan Obat Pada Pasien Gastroesophageal Reflux Disease (Gerd) Rawat Inap Di RS Pertamina Bintang Amin Bandar Lampung - Romaeda, Roz; Nofita, Nofita; Wijaya, Satria (Peneliti.net, 2024)
Gastroesophageal Reflux Disease (GERD) is a disease of the gastrointestinal tract that attacks the stomach, which is caused by the return of contents from the stomach that enter the esophagus, with various signs and symptoms such as Heartburn and regurgitation. This study aims to evaluate the rationality of drug use in Gastroesophageal Reflux Disease (GERD) patients at Pertamina Bintang Amin hospital for the period January - December 2020. This type of research is a descriptive study conducted retrospectively, which collects secondary data in the form of medical records of GERD patients, with a total of 53 samples that have met the inclusion criteria. The results showed that women are more infected with GERD with 43 people (81.1%) and the largest age group in adults (26-45 years) as many as 26 people (49%) and the most work is IRT as many as 19 people (35.8%). And the use of drugs in patients with Gastroesophageal Reflux Disease (GERD) at Pertamina Bintang Amin hospital has been rational with the right indication (100%), the right way of administration (100%), the right patient (100%), the right drug (96,2%), the right dose (96.2%), the right diagnosis (100%), the right assessment of the patient's condition (100%). The use of GERD drugs in inpatients installed Pertamina Bintang Amin hospital as a major has been rationality